Facet‐Dependent and Light‐Assisted Efficient Hydrogen Evolution from Ammonia Borane Using Gold–Palladium Core–Shell Nanocatalysts. Issue 25 (3rd May 2016) - Rej, Sourav; Hsia, Chi‐Fu; Chen, Tzu‐Yu; Lin, Fan‐Cheng; Huang, Jer‐Shing; Huang, Michael H.
Abstract: Au–Pd core–shell nanocrystals with tetrahexahedral (THH), cubic, and octahedral shapes and comparable sizes were synthesized. Similar‐sized Au and Pd cubes and octahedra were also prepared. These nanocrystals were used for the hydrogen‐evolution reaction (HER) from ammonia borane. Light irradiation can enhance the reaction rate for all the catalysts. In particular, Au–Pd THH exposing {730} facets showed the highest turnover frequency for hydrogen evolution under light with 3‐fold rate enhancement benefiting from lattice strain, modified surface electronic state, and a broader range of light absorption. Finite‐difference time‐domain (FDTD) simulations show a stronger electric field enhancement on Au–Pd core–shell THH than those on other Pd‐containing nanocrystals. Light‐assisted nitro reduction by ammonia borane on Au–Pd THH was also demonstrated. Au–Pd tetrahexahedra supported on activated carbon can act as a superior recyclable plasmonic photocatalyst for hydrogen evolution. Abstract : Facets of HER personality : Au–Pd core–shell tetrahexahedral nanocrystals exposing the {730} facet act as efficient plasmonic photocatalyst with the highest turnover frequency value for the hydrogen‐evolution reaction (HER) from ammonia borane under light irradiation.